Out of School Children in Sri Lanka - Chandradasa, W. (My University, 2011)
This paper focuses on the problem of out of school children in Sri Lankan state schools.. It tries to investigate the magnitude of this problem in the Sri Lankan context and also looks at the international scenario. Though the number and proportion of out of school children has reduced over the years in Sri Lanka, it still remains considerably high and needs the attention of educational planners and administrators. Out of school children are defined as the children who are not attending any formal or informal educational institution. The distribution of the number of out of school children varies by gender and region. Poverty is one of the significant causes for the children to be out of school. School related factors like the poor infrastructure, low quality education are other important factors for children not attending a school. Even though gender disparity is not evident in Sri Lanka quality of education needs to be improved to increase the participation of children in school and developmental programmes should be implemented to address the issue of poverty.